Levels and determinants of breast and cervical cancer screening uptake in HIV‐infected women compared with the general population in France. Issue 3 (6th July 2016) - Tron, L; Lert, F; Spire, B; Dray‐Spira, R
Abstract : Objectives: Cancer is a growing concern for HIV‐infected people, and screening plays a major role in alleviating the burden it causes. We sought to investigate the levels and determinants of breast cancer screening (BCS) and cervical cancer screening (CCS) in HIV‐infected women as compared with the general population. Methods: The Agence Nationale de Recherche sur le Sida et les Hépatites Virales (ANRS)‐Vespa2 study was conducted in 2011 in a national representative sample of 3022 HIV‐infected hospital out‐patients in France. The rates and correlates of BCS and CCS among HIV‐infected women were compared with those in the general population using multivariate Poisson regression models. Results: The BCS rate during the 2 years preceding the survey interview was 80.7% among HIV‐infected women vs . 89.1% in the general population ( P  = 0.146). The CCS rate during the preceding 3 years was 88.1% among HIV‐infected women vs . 83.1% in the general population ( P  = 0.021). During the preceding year, the CCS rate among HIV‐infected women was 76.5%. The barriers to BCS and CCS were a low educational level [BCS: adjusted prevalence rate ratio 0.88; 95% confidence interval (CI) 0.80–0.97; CCS: adjusted prevalence rate ratio 0.91; 95% CI 0.83–0.99], not having supplementary health insurance (CCS: adjusted prevalence rate ratio 0.92; 95% CI 0.86–0.98), an irregular gynaecological follow‐up (BCS: adjusted prevalence rate ratio 0.77; 95% CI 0.64–0.92; CCS: adjusted prevalence rate ratio 0.72; 95% CI 0.64–0.81) and a low CD4 count (BCS: adjusted prevalence rate ratio 0.83; 95% CI 0.71–0.97; CCS: adjusted prevalence rate ratio 0.78; 95% CI 0.63–0.98). The disparities in CCS uptake in terms of age, employment and gynaecological follow‐up were less pronounced among HIV‐infected women than in the general population. Conclusions: BCS and CCS uptake was not lower among HIV‐infected women than in the general population, but CCS was suboptimal. Specificities in the profile of barriers to screening emerged.